Hungary at the door of another massive international migration (Academic Journal of Internal Affairs, 2021)
In my study, I present the risk factors that threaten humanity by examining some of the elements affecting the short-term projection of international migration. I examine by data and source literature analysis whether the specific and the ad hoc management of the COVID-19 global epidemic at national level can generate a massive international irregular migration and cause a repeated epidemic threat to the society of transit and host countries. The possibility of a link between international migration and public health epidemic has already been demonstrated by history and medicine, and the situations developed have been addressed in a meaningful way by the countries and organisations concerned. At the same time, in the present social context, also exceptional/arguably measures are taken to the special situation. Such a problematic human disease prevention method could be the release of detainees, which may appear as a new type of irregular release factor.
Keywords: COVID-19; epidemic risk; risk analysis; migration